2020
DOI: 10.1029/2020wr027856
|View full text |Cite
|
Sign up to set email alerts
|

Real Time Control of Rainwater Harvesting Systems: The Benefits of Increasing Rainfall Forecast Window

Abstract: Use of real time control (RTC) technology in rainwater harvesting systems can improve performance across water supply, flood protection, and environmental flow provision. Such systems make the most of rainfall forecast information, to release water prior to storm events and thus minimize uncontrolled overflows. To date, most advanced applications have adopted 24-hr forecast information, leaving longer-term forecasts largely untested. In this study, we aimed to predict the performance of four different RTC stra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 66 publications
0
44
0
2
Order By: Relevance
“…This is of significance when evaluating the differences between urban greening, which is likely to have significant additional ecosystem service benefits to heat reduction, biodiversity and recreation, versus rainwater capture, which is less likely to exhibit these benefits typically associated with urban green space [3,26,29,100,103]. However, it should be noted that recent developments to urban rainwater capture infrastructure, such as community systems, active control and smart technology enabling real time catchment management may also enhance the effectiveness and benefits of capture technology [72,[102][103][104][105][106][107][108], and subsequent research should explore this further.…”
Section: What Do These Results Mean For Stormwater Interventions In the Bay Area?mentioning
confidence: 99%
“…This is of significance when evaluating the differences between urban greening, which is likely to have significant additional ecosystem service benefits to heat reduction, biodiversity and recreation, versus rainwater capture, which is less likely to exhibit these benefits typically associated with urban green space [3,26,29,100,103]. However, it should be noted that recent developments to urban rainwater capture infrastructure, such as community systems, active control and smart technology enabling real time catchment management may also enhance the effectiveness and benefits of capture technology [72,[102][103][104][105][106][107][108], and subsequent research should explore this further.…”
Section: What Do These Results Mean For Stormwater Interventions In the Bay Area?mentioning
confidence: 99%
“…The accuracy of precipitation forecast can be improved by refined precipitation simulation. Xu's research showed that the flood peak time could be delayed with the help of a relatively long prediction time window [64]. Process optimization refers to optimizing the rainwater infiltration and storage facilities, such as combination type, layout area, spatial location and water flow path, which aims to maximize the amount of water stored and optimize the water quality.…”
Section: System Optimizationmentioning
confidence: 99%
“…In this way, the water stored in the stormwater harvesting system can be used to maintain the green roof through the monitoring of soil moisture and an RTC system, while maintaining optimum points of plant growth, as the green roof can treat the water and increase the possibilities of reuse, as for non-potable demands. The addition of stormwater harvesting reservoirs to green roofs can also benefit from reduced runoff and peak flow, especially when used in RTC [28][29][30] Studies show that green roofs can retain stormwater to reduce peak flow and runoff [31][32][33]. In [20], the application of movable gates with RTC was studied in an urban basin to reduce CSO by comparing scenarios using only RTC and RTC combined with passive green roofs.…”
Section: Green Roofmentioning
confidence: 99%